Umniversity virtual world platform for massive open online courses University Platform - Reis, F. (2013)
As lifelong learning takes off and simultaneously financing for education is reduced, new educational practices are being explored namely through the use of information and communication technologies. Massive Open Online Courses (MOOC) are a new way to achieve two main goals: 1) reach as many potential students as possible; 2) use few resources, namely in what teachers/facilitators is concerned. To achieve this it must rely on appropriate technology and on a coherent pedagogical framework. Umniversity virtual world platform aims to better support the particular needs of MOOC. Prepared to manage hundreds or even thousands of students at each course, with asynchronous as well with synchronous tools, it is in the dynamics of the course and the motivation/evaluation of such large numbers of participants that Umniversity makes a difference, integrating seamlessly learning analytics for student self improvement and relying on a connectivist pedagogical approach.